Instrumentalizing Religious Symbolism in Electoral Politics: A Socio-Legal Analysis of Electoral Legitimacy and Post-Election Corruption in Indonesia - Agus Machfud Fauzi; Iffatin Nur; Novi Fitia Maliha; Ahmad Ridwan; Hazim Hazim (Justicia Islamica, 2026)
This study analyzes the paradox between the use of religious symbolism in local election campaigns in Indonesia in 2024 and the corruption committed by several Muslim local leaders after their election. The study employs a qualitative design that combines a normative-juridical approach with comparative socio-political analysis through case studies of five regional heads in East Kolaka, Ponorogo, Central Lampung, Bekasi, and Riau who were arrested by the Corruption Eradication Commission (KPK) in 2025. Normative data were obtained from the literature on siyāsa sharʿiyya, anti-corruption laws and regulations, and official KPK documents. In contrast, empirical data were analyzed using Pierre Bourdieu’s concept of symbolic capital and Max Weber’s theory of charismatic authority. The results indicate that religious symbolism plays an effective role in building electoral legitimacy but does not translate into ethical commitment in governance. Religious identity functions more as political capital than as a foundation for public integrity. These findings suggest that the combination of the instrumentalization of religious symbols and high electoral costs creates incentives for post-election rent-seeking. In practical terms, this study recommends strengthening political integrity through electoral financing reform, ethical oversight of public officials, and the development of leadership indicators that emphasize integrity alongside religious symbolism.